Maltraitance animale et protection de la nature - Emmanuelle Aurenche-Beau (Recherches Germaniques)
This article focuses on Christoph Scheuring’s youth novel Sturm (2020), whose main character is an 18-year-old schoolgirl who is very concerned about animal welfare. The novel tackles the issue of animal abuse in connection with a visit the protagonist makes to the slaughterhouse in the small town in northern Germany where she lives. Her meeting with an environmental activist and her subsequent trip on a fishing boat also raises the issue of the mistreatment of fish and the over-exploitation of natural resources, as illustrated by over-fishing. This paper shows how the novel raises young readers’ awareness of these issues and analyses the way it makes them envision a more respectful relationship with nature. Through the experiences of the main character, the novel also provides a reflection on the possible ways of changing people’s attitudes to nature.